An analytical statistical study to assess the quality of university transportation services: A case study of female students of King Saud University in Riyadh - Aldaham, Suliman Rashed I; Alzeer, Nasser Murshid (Al-Adab Journal, 2022)
1. Study subject: This research presents a statistical analysis of the satisfaction level of female students at King Saud University in Riyadh about using the university transportation. This study subject can be used to design and develop a smart system of university transportation for female students and providing practical solutions applying intelligent transportation technologies and Network Analysis. 2. Objectives of the study: This study seeks to employ the outputs of statistical analysis of random questionnaire dataset consisting of )162 (students distributed over )14) municipalities in Riyadh and )17) colleges at King Saud University in order to improving the quality of university transportation systems using GIS in spatial analysis. The spatial analysis objectives aim to determine the best way to serve female student in moving easily from domicile to the King university and vice-versa. The statistical analysis of the level of female students’ satisfaction is important in enhancing the efficiency of university transportation in order ensure the sustainability and the preservation of university resources. 3. Study methodology: The methodology of this study depends on several sequential and interrelated steps, starting with unloading the questionnaire datasets. In the second step, the distribution pattern of the datasets was tested by applying the tests of normality (Shapiro-Wilk test) to the sample size less than )30) observations, and the (Kolmogorov-Smirnov) to the sample size more than )30) observations. Also (Cronbach’s Alpha coefficient) was applied to testing the internal consistency of the questionnaire contents. 4. Study datasets: This study relied on the questionnaire outputs, which included (74) paragraphs distributed over 10 axes determined by applying the Likert scale. 5. Results: This study reached to determine the distribution pattern of the questionnaire datasets conform to the normal distribution at the significance level of (0.05) and the degrees of freedom of (16) and (162), respectively. The internal consistency of the questionnaire’s contents and was also determined by (the Cronbach’s alpha) coefficient of used (Likert scale). In addition, the general satisfaction about the quality of the university transport service and the factors that help improve its quality with the decisions and recent infrastructure projects of Riyadh city, were identified. 6. Conclusion: This study concluded with many results using the various statistical tests available in the Analyze tools of the descriptive statistics of the (SPSS23) software.